Phytochemical Screening and in vitro Antibacterial Activity of Hibiscus rosa-sinensis L. Leaf Extracts - Dowara, Mregangka; Gogoi, Indrani; Saikia, Shyamalima (Asian Journal of Biological and Life Sciences)
Aim: People have used plants as medicine from the beginning of time to treat a variety of diseases. Different bioactive chemicals found in plants make them viable substitutes for traditional antibacterial treatments. Materials and Methods: Phytochemical analysis was performed to evaluate the phytoconstituents of leaves using standard tests. Agar well diffusion method was used to screened the antibacterial activity of leaf extracts and results were interpreted in terms of diameter of zone of inhibition. Results: The preliminary phytochemical analysis revealed the presence of flavonoids, tannins, steroids, phenolic compounds, saponins in methanolic extract of leaf. In in vitro antibacterial activity screening indicated that all the extracts exhibited inhibitory activity against tested bacteria. Conclusion: The current findings confirm the use of Hibiscus rosa-sinensis L. leaves in traditional medicine to treat conditions like coughs, intestinal tract infections, urinary trat infection, foodborne illnesses and pneumonia caused by these pathogenic bacteria and support the potentiality to serve as a foundation for isolating antibacterial compounds from Hibiscus rosa-sinensis L.
Keywords: Antimicrobial; Phytoconstituents; Traditional medicine; Aqueous extract